2020
DOI: 10.1080/22221751.2020.1725398
|View full text |Cite
|
Sign up to set email alerts
|

DHX9 interacts with APOBEC3B and attenuates the anti-HBV effect of APOBEC3B

Abstract: Hepatitis B virus (HBV) is a partially double-stranded DNA virus that replicates by reverse transcription. We previously demonstrated that the host restriction factor-APOBEC3B (A3B) inhibited HBV replication which was dependent on its deaminase activity during reverse transcription. However, the host factors involved in the process of regulating the anti-HBV function of A3B are less known. In this research, to obtain a comprehensive understanding of the interaction networks of A3B, we conducted coimmunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…In addition to this, DHX9 has been identified as a cytosolic viral DNA sensor in plasmacytoid dendritic cells, dependent on interaction with MyD88 [ 51 ], as well as a viral dsRNA sensor in myeloid dendritic cells [ 52 ], actions that are required to trigger NF-κB activation and subsequent induction of the antiviral cytokine response. In apparent opposition to these protective actions, DHX9 also facilitates the replication of numerous viruses, including hepatitis B virus (HBV) [ 53 , 54 ], hepatitis C virus [ 55 ], human immunodeficiency virus [ 56 ] and chikungunya virus [ 57 ]. In particular regarding HBV, it has recently been revealed that the HBV protein X promotes upregulated DHX9 expression, while DHX9 facilitates HBV DNA replication dependent on an interaction with Nup98 to stimulate DHX9’s helicase activity [ 53 ].…”
Section: Dhx9 General Features and Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to this, DHX9 has been identified as a cytosolic viral DNA sensor in plasmacytoid dendritic cells, dependent on interaction with MyD88 [ 51 ], as well as a viral dsRNA sensor in myeloid dendritic cells [ 52 ], actions that are required to trigger NF-κB activation and subsequent induction of the antiviral cytokine response. In apparent opposition to these protective actions, DHX9 also facilitates the replication of numerous viruses, including hepatitis B virus (HBV) [ 53 , 54 ], hepatitis C virus [ 55 ], human immunodeficiency virus [ 56 ] and chikungunya virus [ 57 ]. In particular regarding HBV, it has recently been revealed that the HBV protein X promotes upregulated DHX9 expression, while DHX9 facilitates HBV DNA replication dependent on an interaction with Nup98 to stimulate DHX9’s helicase activity [ 53 ].…”
Section: Dhx9 General Features and Functionsmentioning
confidence: 99%
“…In particular regarding HBV, it has recently been revealed that the HBV protein X promotes upregulated DHX9 expression, while DHX9 facilitates HBV DNA replication dependent on an interaction with Nup98 to stimulate DHX9’s helicase activity [ 53 ]. Another recent study also revealed that DHX9 promotes HBV DNA replication via inhibiting the apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like 3B (A3B), which usually functions to impede HBV DNA replication [ 54 ].…”
Section: Dhx9 General Features and Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An intriguing connection of HBx to APOBEC3B was identified by Shen et al (2020) and demonstrated the up-regulation of DHX9 proteins by HBx. In their related study, Chen et al (2020) reported that DHX9 suppresses APOBEC3B and inhibited the anti-HBV effects. Additionally, HBx post-translational suppression of APOBEC3G has been shown within Huh7 cells (Chen et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…La protéine X diminue également le niveau intracellulaire d'A3G en favorisant son externalisation par la voie exosomale, indépendamment de sa dégradation par le protéasome ou le lysosome [338]. L'hélicase DHX9 (DExH-Box Helicase 9) s'associe à A3B et inhibe son activité restrictive en perturbant la liaison d'A3B à l'ARNpg [339]. De plus, l'ARN long non codant HULC (Hepatocellular carcinoma Up-regulated Long non-Coding RNA), fortement exprimé dans le cas de carcinome hépatocellulaire (HCC), favorise l'expression du miARN-539 qui cible la 3'UTR de l'ARNm d'A3B, entraînant la dégradation de la protéine [340].…”
Section: Le Virus T-lymphotropique Humain (Htlv)unclassified